The validity and intra-tester reliability of markerless motion capture to analyse kinematics of the BMX Supercross gate start - Grigg, J.; Haakonssen, E.; Rathbone, E.; Orr, R.; Keogh, J. W. L. (Sports Biomechanics, 2018)
The aim of this study was to quantify the validity and intra-tester reliability of a novel method of kinematic measurement. The measurement target was the joint angles of an athlete performing a BMX Supercross (SX) gate start action through the first 1.2 s of movement in situ on a BMX SX ramp using a standard gate start procedure. The method employed GoPro® Hero 4 Silver (GoPro Inc., USA) cameras capturing data at 120 fps 720 p on a `normal` lens setting. Kinovea 0.8.15 (Kinovea.org, France) was used for analysis. Tracking data was exported and angles computed in Matlab (Mathworks®, USA). The gold standard 3D method for joint angle measurement could not safely be employed in this environment, so a rigid angle was used. Validity was measured to be within 2°. Intra-tester reliability was measured by the same tester performing the analysis twice with an average of 55 days between analyses. Intra-tester reliability was high, with an absolute error <6° and <9 frames (0.075 s) across all angles and time points for key positions, respectively. The methodology is valid within 2° and reliable within 6° for the calculation of joint angles in the first ~1.25 s. ABSTRACT FROM AUTHOR